Pengaruh Kompetensi dan Penggunaan Teknologi Informasi Terhadap Kinerja Pegawai dengan Semangat Kerja Sebagai Variabel Intervening Pada Kantor Camat Kecamatan Tanjung Emas - Muhammad Albarkah; Vicky Brama Kumbara; Nia Nahdila (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the effect of competence and information technology utilization on employee performance with work morale as an intervening variable at the Tanjung Emas District Office. The study employed a quantitative approach using a survey method. The population consisted of all employees of the Tanjung Emas District Office, and a saturated sampling (census) technique was applied, in which all population members were selected as respondents. Data were collected through a structured questionnaire using a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that competence has a positive and significant effect on both work morale and employee performance. In contrast, information technology utilization has a positive but insignificant effect on work morale and employee performance. Work morale also has a positive and significant effect on employee performance. Furthermore, the indirect effect analysis reveals that work morale successfully mediates the relationship between competence and employee performance but fails to mediate the relationship between information technology utilization and employee performance. These findings suggest that improving employee competence is a key factor in enhancing work morale and performance, while the contribution of information technology utilization requires stronger digital capabilities, continuous training, and more effective technology implementation to optimize organizational performance.